Extracorporeal shockwave therapy as a treatment option for shoulder impingement syndrome: a systematic review and meta-analysis - Ahmad Aldardour; Ahmad R. Al-Qudimat; Mohammad Etoom; Shefa’a Alnammaneh; Wesam al Debes; Loiy Khasaweneh; Alaa Abd-Alrazaq; Sunitha Mysore; Muhammed Al-Jarrah (Bulletin of Faculty of Physical Therapy)
Abstract Background Shoulder impingement syndrome (SIS) is a common alignment syndrome that causes significant discomfort and functional limitations. In recent years, extracorporeal shock wave therapy (ESWT) has gained attention as a promising non-invasive treatment for SIS. However, its effectiveness remains controversial. This review aimed to elucidate the efficacy of ESWT in SIS by analyzing data from randomized controlled trials (RCTs). Material and methods A systematic review of randomized controlled trials (RCTs) was conducted. Search sources included 3 databases, the references list of the included studies that cited the included studies. In total, 2 reviewers (S.N. and L.K.) independently conducted the study selection. W.D. and A.A. carried out data extraction, risk of bias assessment, and quality of evidence appraisal. Extracted data were synthesized using a statistical approach (standard meta-analysis methodologies). A random-effects model was employed to account for potential heterogeneity across studies. Effect sizes were reported as standardized mean differences (SMD) with corresponding 95% confidence intervals (CI). Heterogeneity was assessed using Cochran’s Q test, with statistical significance set at p < 0.05, and quantified using I 2 statistics. Results Our meta-analysis revealed that all four included studies (100%) showed a low risk of bias across all five assessed domains, indicating strong methodological quality and reliability of the findings. Furthermore, this meta-analysis revealed that ESWT significantly reduced pain in patients with SIS over 2–3 months. The pooled analysis demonstrated a marked improvement in pain 2.18 (95% CI: 0.45 to 3.90, I 2 = 0%). Furthermore, the ESWT group demonstrated a significant difference from the other interventional group in terms of SPADI alleviation in 2–3 months 19.46 (95% CI: 5.12 to 33.79, I 2 = 0%). Conclusion This review and meta-analysis highlighted that shockwave therapy is more efficient than other interventions in reducing pain and enhancing functional activities in adults with SIS in 2–3 months period. This systematic review supports the integration of ESWT protocols into clinical practice based on symptom severity and chronicity of SIS. The findings offer valuable guidance for future research and highlight the need for standardized approaches to optimize treatment outcomes.